The impact of strategic planning on mission achievement in Egyptian nonprofit organizations: an assessment using the balanced scorecard approach - Ghoneim, Nashwa (AUC Knowledge Fountain, 2012)
The relationship between strategic planning and organizational performance has rarely been examined in the public and nonprofit sectors. Moreover, most of the existing research has been confined to examining the nonprofit sector in the western society and very little has been conducted about strategic planning in nonprofits in developing countries like Egypt. This study empirically examines the effect of strategic planning on Egyptian nonprofit organization's performance effectiveness. An assessment of performance effectiveness was made using the multiple perspectives of the balanced scorecard. A fifth dimension was added to the balanced scorecard, developed originally by Niven (2008), which is volunteers' development. A retrospective cross sectional survey research design was used to compare the performance of strategic planning nonprofits versus that of non strategic planning nonprofits. A purposive sample of forty Egyptian nonprofit organizations was selected for participation in the study. Results have indicated a statistically significant difference between the mean composite scores of strategic planning activities in strategic versus non-strategic planning nonprofits along four out of five domains of the BSC performance effectiveness scale. These domains were namely; customer processes, internal business processes, employees learning and growth, volunteers' development except for financial processes. Results however, did not show that most of the Egyptian nonprofits are fully aware of the BSC as a tool for assessing their performance effectiveness.